Analysis of Factors that Influence Financial Distress Conditions using the Debt Service Coverage Ratio Approach (Case Study of the Food and Beverage Industry Listed on the Indonesian Stock Exchange Before and During Covid-19) - Wicaksono, Matius Rangga; Bandono, Bayu; Achsani, Noer Azam (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Covid-19 condition is known to have had a major impact on the financial performance of issuers. The food and beverage industry is one of the mainstay manufacturing sectors in making a major contribution to national economic growth. The data used in this study was pre-covid data, year 2018 until 2021 during covid. The method used in this study is the Debt Service Coverage Ratio Pranowo et al. (2010). The analysis used in this research is descriptive analysis and panel data regression. The results of this research were that 26 company experienced a decrease in distress, 26 company experienced an company in Profitability, 26 company experienced an increase in Liquidity, 26 company experienced an increase in Efficiency, 26 company experienced a decrease in Leverage, 26 company experienced a decrease in Solvency. Factors that show a significant influence on financial distress in the period before Covid-19 are Efficiency, Liquidity. The factor of increasing efficiency also influences the reduction in the occurrence of financial distress. The factor of increasing liabilities also influences the increase in the occurrence of financial distress. Factors that show a significant influence on financial distress during Covid-19 are Solvability and Efficiency. This shows that during Covid-19, the increase in the value of debt will influence the tendency to increase the occurrence of financial distress. The decline in the value of income during Covid-19 also influenced the increase in financial distress. Advice to investors to be more selective in choosing food and beverage issuers as a place to invest during Covid-19. One important consideration is that investors focus more on factors that have a significant influence on Liquidity, Efficiency, Solvency.